Climatic changes during the deposition of "Arctica Islandica Clays andnSands" fm (Lower Pleistocene): evidences from the lower Cecina Valley (Tuscany, Italy) - Ciampalini A.; Consoloni I.; SARTI, GIOVANNI (Brigati, 2007)
The Lower Cecina valley is part of a neogenic extensional basin, located in southern Tuscany. I t is mainly lengthened in E-W direction an d yielded by extensional tectonics which interested the whole occidental side of the Apenines since upper Tortonian. In the study area, comprised between Riparbella and Casale Marittimo, outcrops a remarkable thickness of Lower to Middle Pleistocene deposits that lye in unconformity whether ofiolitic rock or Pliocenic deposits. The "Arctica islandica clays and sands" fm represents the older of the litostratigraphic units recognized on the basis of geologica! survey and facies analysis. It is organized in a transgressive-regressive cycle recording the transition from an upper-lower shoreface to a fluvio-influenced depositional environment. The transgressive sands contain a lot of micro- and macrofossils between which two of climatic significance as the bivalve Arctica islandica and the coral referable to Cladocora caespitosa species. The two taxa are placed at different stratigraphic positions. In fact, while ali the specimen of Arctica islandica were founded at the base of the Fm, in the first 5 m, beds of Cladocora caespitosa occur upwards. Arctica islandica lives today over 65° oflatitude with a temperature ranging between 4°C and 13°C and thus its presence, in the deposits lying immediately over the transgression surface, witness cold temperature. The present-day distribution of Cladocora caespitosa is instead ranging between l5°C and 22°C of average temperature and prefers sites exposed to fine sediments and alluvial inputs. Thus a phase of warming seems to have occurred during the deposition of the "Arctica Islandica clays and sands" fm and the Cladocora caespitosa beds can be related to the maximum flooding conditions at the end of the transgressive phase.